Altered intestinal barrier contributes to cognitive impairment in old mice with constipation after sevoflurane anesthesia - Zhao, Tianyun; Lu, Junming; Qin, Jingwen; Chen, Yanxin; Shi, Ziwen; Wei, Wei; Xiong, Peng; Ma, Daqing; Song, Xingrong (Frontiers in Nutrition, 2023)
The elderly patients have a high risk to develop postoperative cognitive dysfunction (POCD). Gastrointestinal disorders such as constipation in aged population may be involved in the pathogenesis of neurological disorders by promoting inflammatory responses due to a 'leaky gut'. General anesthetic sevoflurane may impair gastrointestinal function in elderly to trigger neurological complications following surgery. Therefore, we hypothesized that aged individuals with gastrointestinal dysfunction may be more vulnerable to sevoflurane and consequently develop POCD.: Aged mice were randomly divided into four groups: Control (CTRL), CTRL+sevoflurane (Sev), slow transit constipation (STC), and STC+Sev. Mice in the STC and STC+Sev groups were intra-gastrically administrated loperamide (3 mg/kg, twice a day for 7 days) to induce a slow transit constipation (STC) model determined with fecal water content and the time of first white fecal pellet and others received the similar volume of saline. One week later, mice in the CTRL+Sev group and STC+Sev received 2% sevoflurane for 2 hrs. The gut permeability evaluated with 4-kDa fluorescein isothiocyanate (FITC)-dextran, serum cytokines, microglia density, TLR4/NF-κB signaling expression and POCD-like behavioral changes were determined accordingly. RESULTS: The loperamide-induced STC mice had decreased fecal water content and prolonged time of first white fecal pellet. Sevoflurane exposure caused significantly increased gut permeability and serum cytokines, and microglia and the TLR4/NF-κB signaling pathway activation in the prefrontal cortex of the aged STC mice. Sevoflurane also caused cognitive 2 2 impairment and emotional phenotype abnormality in aged STC mice.CONCLUSION: Aged STC mice were more vulnerable to sevoflurane anesthesia and consequently developed POCD-like behavioral changes. Our data suggest that gastrointestinal disorder including constipation may contribute to the POCD development.